Psychotherapies for the Treatment of Bipolar Disorder - Metin Çınaroğlu (Psikiyatride Güncel Yaklaşımlar, 2024)
Bipolar disorder is one of the major mental disorders leading to disability. This review aims to highlight the most effective psychotherapies used in the treatment of bipolar disorder. Across diverse schools of psychology, five psychotherapeutic approaches have emerged as both highly utilized and effective. These are interpersonal social rhythm therapy, psychoeducation, cognitive-behavioral therapy, family-focused therapy and mindfulness therapy. Multiple randomized controlled trials focusing on these psychotherapeutic interventions have provided strong evidence of their effectiveness when delivered alongside standard care. The results suggest that these approaches have a constructive role to play as adjunctive models of psychotherapy in the management of bipolar disorder. While the available evidence is robust, further randomized clinical trials are needed. Expanding these studies to sub-areas such as geriatrics and adolescents would provide more detailed information on the feasibility and efficacy of these psychotherapies among different demographic groups.